1943
DOI: 10.1021/ja01243a019
|View full text |Cite
|
Sign up to set email alerts
|

A New Modification of the Ullmann Synthesis of Fluorene Derivatives

Abstract: moved and the residual viscous red oil treated with 5 cc. of boiling petroleum ether (b. p. 60-110"). The insoluble dark gum was removed from the solution by decantation of the latter. On cooling, the petroleum ether deposited an orange-colored solid which weighed 235 mg. By concentrating the mother liquors, carefully discarding the red gum which formed regularly, another 540 mg. of this solid was obtained. The total yield was 775 mg. (26%). A sample was recrystallized from petroleum ether (Darco) to constant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

1962
1962
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…Determined in acetone-ds (except 40 in MeOH-d4). Preparation described in [47], but no data presented there. Described in [441, m.p.…”
Section: ")mentioning
confidence: 99%
“…Determined in acetone-ds (except 40 in MeOH-d4). Preparation described in [47], but no data presented there. Described in [441, m.p.…”
Section: ")mentioning
confidence: 99%
“…It was found that 59% 3-(2-acetamido)-naphthyl phenyl ketone [14] was isolated when b-acetylnaphthylamine was reacted with phenylmethanol as substrates (entry 9).…”
mentioning
confidence: 99%
“…For the preparation of I-methyl-fluorenone (VII) the treatment of 2-chloro-2'methylbenzophenone with potassium hydroxide in quinoline [13] and the diazotization and "Verkochung" of2-amino-2'-methylbenzophenone [14,15] have been pro-424 (I) I. GOSNAY ET AL.…”
Section: 1'-dimethyl-dibiphenylene-ethene (I X = Ch 3 )mentioning
confidence: 99%